Exploring the relationship between compressed work hours satisfaction and absenteeism in front-line service work. Issue 1 (2nd January 2017) - Deery, Stephen; Walsh, Janet; Zatzick, Christopher D.; Hayes, Andrew F.
Abstract: There has been an upsurge of interest in compressed workweek schedules because of the opportunities they provide for enhanced organizational efficiency and more balanced work and life roles for employees. This study tested a moderated mediation model of the effects of compressed work hours satisfaction on absenteeism with the purpose of exploring both the mediation effects of emotional exhaustion and physical health and the moderating effects of sex on this relationship. It utilized data drawn from a sample of 236 contact-centre service workers linked to absenteeism data collected for a period of 12 months following the survey. Results indicated that compressed work hours satisfaction was associated with lower absenteeism and that this relationship was mediated sequentially through emotional exhaustion and physical health. Although the indirect effect of compressed work hours satisfaction on absenteeism through emotional exhaustion and physical health was not significantly different between women and men, the relationship between compressed work hours satisfaction and physical health was positive for women but not for men. The implications of these findings are discussed.